Simulations of satellite tidal debris in the Milky Way halo - Mazzarini, Matteo; Just, Andreas; Macciò, Andrea V.; Moetazedian, Reza (Astronomy and astrophysics, 2020)
Aims. We study the distribution of the stellar and dark matter debris of the Milky Way satellites.Methods. For the first time we address the question of the tidal disruption of satellites in simulations by utilising simultaneously (a) a realistic set of orbits extracted from cosmological simulations; (b) a three-component host galaxy with live halo, disc, and bulge components; and (c) satellites from hydrodynamical simulations. We analyse the statistical properties of the satellite debris of all massive galaxies reaching the inner Milky Way on a timescale of 2 Gyr.Results. Up to 80% of the dark matter is stripped from the satellites, while this happens for up to 30% of their stars. The stellar debris ends mostly in the inner Milky Way halo, whereas the dark matter debris shows a flat mass distribution over the full main halo. The dark matter debris follows a density profile with inner power law index αDM = −0.66 and outer index βDM = 2.94, while for stars α* = −0.44 and β* = 6.17. In the inner 25 kpc the distribution of the stellar debris is flatter than that of the dark matter debris, and the orientations of their short axes differ significantly. Changing the orientation of the stellar disc by 90° has a minor impact on the distribution of the satellite debris.Conclusions. Our results indicate that dark matter is more easily stripped than stars from the Milky Way satellites. The structure of the debris is dominated by the satellite orbital properties. The radial profiles, the flattening, and the orientation of the stellar and dark matter debris are significantly different, which prevents the prediction of the dark matter distribution from the observed stellar component.
Gesehen am 03.06.2020